PERAN SIKAP PROFESIONALISME AUDITOR INTERNAL DALAM MENGUNGKAPKAN TEMUAN AUDIT - NATALIA, DEVINA (: 2303-1719)
Nowadays the growth of business is increasing, it shows with many companies establish. Company is established to gain profits and make it keep survive. Company does many efforts to reach it. Internal auditor is needed by company during reach its purposes, with gives systematic discipline approaching to evaluate and to increase risk management effectiveness, controlling and manner process. During their operational, auditor internal often finds auditors findings. For reach those results, internal auditor should has professional characteristic. Internal auditor is expected to apply and support main principals of professionalism, such as : integrity, objectivity, secrecy, and competency. This research is to learn and know the professional’s role of internal auditor to auditors finding. Professional auditor will resulting good quality and correct findings, details, high accuracy and internal auditor must give their best loyalty to the company.